A contribution to the human capital investment debate vis-à-vis economic growth: the case for Nigeria - Lasbrey ANOCHIWA (Annals of Human Resource Management Research, 2021)
Purpose: Human capital development is essentially vital in enhancing economic growth and Nigeria needs to grow. This study investigates the contribution of human capital to growth in Nigeria. Research methodology: We have disaggregated the article's variables into different models, for a better result. We employed the Autoregressive Distribution Lag (ARDL) framework to examine the relationship between the variables. E-views software was used as applied in Akbari, Chude and Chude (2013). Result: The result shows that there exists a long-run relationship between the human capital indices, education and health in Nigeria and economic growth. Though the coefficient is positive but has a statistically insignificant relationship with human capital development and economic growth. Limitation: The study was hindered by the availability of data. Contribution: It is satisfactory to know from the study that human capital is still relevant in explaining growth in Nigeria. Keywords: Human capital, Economic growth, Development